Trends and Innovations in the Development of Inquiry-Based Science Modules: A Systematic Literature Review - Munib, Munib; Jufri, Wahab; Purwoko, Agus Abhi; Mahrus, Mahrus; Rokhmat, Joni; Sukarso, AA (Journal of Science and Science Education, 2025)
Natural Science (IPA) learning in the 21st century requires students to not only understand science concepts, but also to have 21st century skills such as critical thinking, collaboration, and technological literacy. To answer these challenges, the inquiry learning approach is one of the strategic solutions because it encourages active involvement of students in building knowledge through the scientific process. Inquiry-based learning modules are also rapidly developing as a medium that supports active, contextual, and flexible learning. This research aims to conduct a systematic literature review (SLR) on trends and innovations in the development of inquiry-based science modules. The study was conducted using the SLR method based on the PRISMA guidelines, by analyzing 35 articles published between 2015–2025. The results of the study show that Research and Development (R&D) methods, especially the 4D and ADDIE models, are the most widely used approaches. The inquiry model, especially guided inquiry, is the dominant approach that has proven to be effective in improving students' science process skills, literacy, and critical thinking. Various innovations were identified, including the integration of STEM approaches, PjBL, ethnoscience, as well as the development of digital modules such as e-modules and interactive flipbooks. This study highlights the importance of innovation and contextualization in the development of inquiry-based science modules to improve the quality of learning in accordance with the demands of the Merdeka curriculum and the times